Vasospasm after Subarachnoid Hemorrhage: Diagnosis with MR Angiography - Grandin, Cécile B.; Cosnard, Guy; Hammer, Frank; Duprez, Thierry P.; Stroobandt, Guy; Mathurin, Pierre (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: The possibility of treating intracranial vasospasm has increased the significance of its diagnosis and follow-up; however, so far, no ideal method is available. The goal of this study was to assess the accuracy of MR angiography versus intraarterial angiography (IA-DSA) in detecting vasospasm.METHODS: The study included 42 patients with acute spontaneous subarachnoid hemorrhage (SAH). Serial MR angiograms (minimum, two per patient within 10 days after the event; total, 149) were obtained prospectively using a 3D time-of-flight technique covering the circle of Willis at 0.5 T. Forty-seven MR angiograms could be compared with intraarterial angiograms obtained within 24 hours of MR angiography. Vascular narrowing on both studies was rated consensually by two pairs of neuroradiologists using a scale from 0 (no narrowing) to 3 (severe narrowing). Categories 0 and 1 were considered an absence of vasospasm and categories 2 and 3 a presence of vasospasm.RESULTS: Agreement between MR angiography and IA-DSA (assessed with weighted κ statistics) was substantial for the middle and anterior cerebral arteries (MCA and ACA) but moderate for the internal carotid artery (ICA). The sensitivity, specificity, accuracy, and positive and negative predictive values of MR angiography for detecting patients with vasospasm were 92%, 98%, 96%, 92%, and 98%, respectively. Considering each vessel separately, specificity was high for all locations (95–99%) and sensitivity was excellent for the ACA (100%) but poorer for the ICA (25%) and MCA (56%).CONCLUSION: MR angiography at 0.5 T is capable of identifying vasospasm after acute SAH but is less sensitive than IA-DSA for depicting vasospasm in the ICA and MCA.